2020
DOI: 10.1101/2020.05.01.069807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxygen radicals and cytoplasm zoning in growing lily pollen tubes

Abstract: Recently redox-regulation of tip growth has been extensively studied, but differential sensitivity of growing cells to particular ROS and their subcellular localization is still unclear.Here we used specific dyes to provide mapping of H 2 O 2 and O • 2¯ in short and long pollen tubes. We found apical accumulation of H 2 O 2 and H 2 O 2 -producing organelles in the shank that were not colocalized with O • 2¯-producing mitochondria. Differential modulation of ROS content of the germination medium affected both g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In addition, pollen‐tube rupture and sperm release were mediated by high levels of ROS at the entrance to the female gametophyte (Duan et al ., 2014). Different ROS can be considered to exhibit accelerating or decelerating influences on pollen‐tube growth, which possibly act in vivo as positive or negative signals controlling pollen physiology (Podolyan et al ., 2020). We observed that ROS became active in the endomembrane of rice pollen grain once it hydrates and is apically distributed in growing pollen tubes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pollen‐tube rupture and sperm release were mediated by high levels of ROS at the entrance to the female gametophyte (Duan et al ., 2014). Different ROS can be considered to exhibit accelerating or decelerating influences on pollen‐tube growth, which possibly act in vivo as positive or negative signals controlling pollen physiology (Podolyan et al ., 2020). We observed that ROS became active in the endomembrane of rice pollen grain once it hydrates and is apically distributed in growing pollen tubes.…”
Section: Discussionmentioning
confidence: 99%